Akhlakul Karimah Rasulullah Saw dalam Bermu’amalah Ma’a al-Nas Menurut M. Quraish Shihab dalam Tafsir al-Mishbah - Lubna Mufidah; Encung Encung (Medan Resource Center, 2023)
Islam is a comprehensive religion that encompasses various aspects of human life, including faith, worship, morals, and interactions (muamalah). Prophet Muhammad (SAW) was sent to this world as a perfect exemplar of good morals, guided by Allah (SWT), and was able to transform negativity into positivity. However, in today's modern era, there is a decline in moral values among teenagers and children, partly due to the failure of education to instill good morals in individuals. Thus, this study aims to explore M. Quraish Shihab's perspective on the noble character (Akhlaq Al-Karimah) of Prophet Muhammad (SAW) in his interactions with people (muamalah) as presented in his interpretation, Tafsir Al-Misbah. The researcher chose Al-Misbah's interpretation due to its detailed insights compared to other interpretations. This study adopts a library research methodology with a focus on character analysis. Through this investigation, it was discovered that the Qur'an addresses Akhlaqul Karimah in three main aspects: education (Surah Al-Alaq, verses 1-5), marriage (Surah An-Nisa', verse 19), and commerce (Surah Al-Baqarah, verse 275).